Pengaruh Kesadaran Perpajakan Dan Sanksi Pajak Terhadap Motivasi Wajib Pajak Untuk Memenuhi Kewajibannya Di CV. Signart Advertising - Ihdina Agustina; Muammar Rinaldi (lppm.eka-prasetya.ac.id, 2020)
This study aims to determine the effect of Tax Awareness and Tax Sanctions against Motivation of Taxpayers to Fulfill Their Obligations on the CV. Signart Advertising. The population on this research is individual taxpayer on the CV. Signart Advertising. Samples taken as many as 50 respondents by using saturation sampling. The results of the research analysis show that Tax Awareness partially has effect on Motivation of Taxpayers to Fulfill Their Obligations on the CV. Signart Advertising. The results of the research analysis show that Tax Sanctions has no effect significantly on Motivation of Taxpayers to Fulfill Their Obligations on the CV. Signart Advertising. The results showed that Tax Awareness and Tax Sanctions simultaneously have significant effect on Motivation of Taxpayers to Fulfill Their Obligations on the CV. Signart Advertising. The results of this study are supported by the value of R square (R2) which means Tax Awareness and Tax Sanctions have an effect on Motivation of Taxpayers to Fulfill Their Obligations on the CV. Signart Advertising. While the remaining is effected by other factors originating from outside this research model such as Fiscus Service and Tax Rate.